2021
DOI: 10.3390/diagnostics11112008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Characteristics of Hyaline-Vascular Type Unicentric Castleman Disease: A 20-Year Retrospective Analysis

Abstract: The first case of hyaline vascular type of unicentric Castleman disease (HV-UCD) was reported more than six decades ago. Since patients with HV-UCD are often asymptomatic and this condition is generally discovered incidentally on imaging tests, most of the previous reports were of mediastinal origin detected by chest radiography. In recent years, improved access to imaging modalities has provided new insights in the diagnosis of this condition. In this study, we reviewed the detailed clinical and pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…However, we recently reported that intra-abdominal and retroperitoneal origins are more frequent than previously thought. 36 In the cohort of 38 cases, the most common location was the abdominal cavity (34.2%), followed by mediastinal (23.7%) and retroperitoneal (15.8%) regions. 36 In the abdominal cavity, the mesenteric origin is the most common and is often clinically excised due to suspicion of gastrointestinal stromal tumor, leiomyoma, or neurogenic tumor.…”
Section: Histological Featuresmentioning
confidence: 90%
See 3 more Smart Citations
“…However, we recently reported that intra-abdominal and retroperitoneal origins are more frequent than previously thought. 36 In the cohort of 38 cases, the most common location was the abdominal cavity (34.2%), followed by mediastinal (23.7%) and retroperitoneal (15.8%) regions. 36 In the abdominal cavity, the mesenteric origin is the most common and is often clinically excised due to suspicion of gastrointestinal stromal tumor, leiomyoma, or neurogenic tumor.…”
Section: Histological Featuresmentioning
confidence: 90%
“… 36 In the cohort of 38 cases, the most common location was the abdominal cavity (34.2%), followed by mediastinal (23.7%) and retroperitoneal (15.8%) regions. 36 In the abdominal cavity, the mesenteric origin is the most common and is often clinically excised due to suspicion of gastrointestinal stromal tumor, leiomyoma, or neurogenic tumor. The mean size of the lesions is approximately 5.0 cm, 35 , 36 which is larger than the lymph nodes observed in MCD.…”
Section: Histological Featuresmentioning
confidence: 90%
See 2 more Smart Citations
“…Systemic symptoms are present in a small percentage of cases of UCD, and IL-6 appears to be the responsible cytokine, being better characterized in MCD, where these symptoms predominate [ 3 , 5 ] .…”
Section: Discussionmentioning
confidence: 99%